NEAREST NEIGHBOR PATTERNS OF DOMINANT TREE SPECIES IN TROPICAL FORESTS, PHOU KHAO KHOUAY NATIONAL PARK, LAOS - Hong Hai, Nguyen; Phomphoumy, Khamphet; Van Quy, Nguyen (Journal of Forestry Science and Technology, 2023)
Target-tree management is a silviculture technique that aims to achieve sustainable forest management by considering the spatial structure of forests. In this study, a new quantitative method was used to analyze the spatial structure of natural forest stands in the Phou Khao Khouay national park in Laos. The method involved mapping and measuring all individual trees with a diameter at breast height (DBH) greater than or equal to 5 cm in 32 permanent plots of 50 m × 50 m. The analysis focused on four spatial structural parameters: uniform angle index, species mingling, height dominance, and crowding. The results showed that (1) the dominant species in the three forest types had a species mingling degree ranging from medium to complete mixture; (2) the target trees were found to have a dominant height compared to their nearest neighbors; (3) the distribution patterns of trees in the stands varied from regular to clumped; and (4) the crowding index indicated a distribution density of trees from sparse to dense. Dispersal limitation and competition among neighboring trees were the main mechanisms driving the forest’s spatial structure in the study area. The findings of the present study provide valuable information for proposing silvicultural measures that promote sustainable forest management in Phou Khao Khouay National Park. By understanding the spatial structure of forests, target-tree management can be used to improve forest health, increase biodiversity, and enhance the ecosystem services provided by forests.